School Is Closed : Simulating the Long-Term Impact of the COVID-19 Pandemic–Related School Disruptions in Kuwait - Bilo, Simon (Washington, DC: World Bank, 2022)
The schooling disruption caused by COVID-19 in Kuwait is among the longest in the world. Using the similarities between the schooling disruptions due to the Gulf War and the schooling disruption due to the COVID-19 pandemic, this note shows that students in school during the COVID-19 pandemic face significant reductions in the present value of their lifetime income. Furthermore, the findings show that students in higher grades during the pandemic are likely to face larger reductions in lifetime earnings than students in lower grades. Kuwaiti females in secondary school who will become civil service workers face a reduction of close to $40,000. The corresponding reduction for males is more than $70,000.